Retinal obliterative vasculitis associated to contralateral retinal neovascularization in membranoproliferative glomerulonephritis - Nicolai, Michele; Franceschi, Alessandro; Lassandro, Nicola Vito; Pelliccioni, Paolo; Danieli, Luca; Pirani, Vittorio; Mariotti, Cesare (European journal of ophthalmology, 2022)
To report our experience with a peculiar case of asynchronous bilateral retinal vascular occlusion in a patient suffering from membranoproliferative glomerulonephritis. A 57-year-old dialysed male affected by membranoproliferative glomerulonephritis who underwent kidney transplantation complained of a sudden vision loss in his right eye (RE). His best-corrected visual acuity (BCVA) was 20/40 in RE and 20/20 in the left eye (LE); ophthalmological and fluorangiographic examinations revealed unilateral retinal obliterative vasculitis with panuveitis and apparent sparing of contralateral eye. About 6 months later the patient developed a branch retinal vein occlusion associated with a papillary neovascular membrane in LE. Corticosteroid therapy was administered and immunosuppressant dosage was increased with macular oedema reduction in both events. We report a case of unilateral retinal obliterative vasculitis and subsequent contralateral retinal neovascularization and branch retinal vein occlusion in a patient affected by membranoproliferative glomerulonephritis.